Digital-Based Transformation of Islamic Religious Education Learning in the Society 5.0 Era - Muslimin Muslimin (Al-Ilmu, 2026)
This article examines the digital transformation of Islamic Religious Education (PAI) in the Society 5.0 era as a human-centered, value-based, and technology-supported learning model. The background of the study arises from the need to align PAI with the learning characteristics of digital native students while preserving Islamic moral and spiritual values amid rapid technological change. This study employs a qualitative library research design by analyzing accredited journal sources related to digital learning, Islamic values, and pedagogical innovation in PAI. Data were collected through systematic documentation and analyzed using thematic content analysis to identify patterns linking technology integration, value preservation, and innovative pedagogy. The findings reveal that digital tools such as LMS, gamification, interactive media, and immersive technologies can enhance engagement and understanding when integrated with Islamic digital ethics, moderation values, and reflective learning approaches. The discussion highlights that challenges related to infrastructure, teacher competence, and moral risks in digital spaces require TPACK-based training, adaptive pedagogy, and explicit ethical guidance. In conclusion, digital transformation in PAI is not merely technological adaptation but a strategic pathway to strengthen character formation, religious moderation, and meaningful learning within a human-centered framework aligned with Society 5.0